Etika Kecerdasan Buatan dalam Perspektif Teologi Kristen: Implikasi bagi Pendidikan Agama di Era Society 5.0 (Studi pada Mahasiswa Teologi) - Tri Subekti; Pujiwati Pujiwati; Indriati Tjipto Purnomo (Sekolah Tinggi Teologia Kerusso Indonesia, 2026)
This study aims to analyze the use of generative artificial intelligence (GenAI) among theology students and its ethical and theological implications for theological education in the Society 5.0 era. The study employs a light mixed-methods approach with a sequential explanatory design, involving theology students as survey and interview participants. The findings show that GenAI is primarily used as a tool to understand course materials, seek initial explanations, develop ideas, and complete academic assignments. Although students demonstrate awareness of potential bias, dependency, plagiarism, and other ethical risks, practices of transparency, information verification, and critical reflection have not been carried out consistently. The concept of imago Dei is relevant as a theological lens for evaluating technology use because it affirms human dignity, responsible freedom, and moral accountability in academic practice. This study concludes that GenAI can support theological learning constructively when used wisely, integrated with Christian faith-based ethical literacy, and strengthened through clear institutional policies, lecturer guidance, and an academic culture that upholds integrity, discernment, and accountability.